Institutional Management of Peer-Led Learning: A Framework for Holistic Integration - Jason Eyre (Association for Learning Development in Higher Education (ALDinHE), 2015)
If we are to accept that peer-led learning (peer mentoring, peer tutoring and related approaches) are of benefit to students, how are we to approach the implementation of such approaches at the institutional level in a way that is resource efficient and effective? This paper presents the holistic framework for the institution-wide coordination and support of a wide variety of peer-led learning initiatives developed at De Montfort University. The framework presented sidesteps the thorny issues of categorisation that dominate the discourse of peer-led learning by devolving issues of definition to the site of implementation. A simplified typology is presented that characterises an initiative based on its level of formality and its overarching purpose with respect to transformational Ã¢â¬Ëtransition pointsÃ¢â¬â¢ through the student lifecycle. This Ã¢â¬Ëmixed economyÃ¢â¬â¢ approach accommodates highly idiosyncratic and locally-defined approaches to peer-led learning coordinated and supported by the universityÃ¢â¬â¢s learning development unit (the Centre for Learning and Study Support).